Anemia among patients admitted to the Emergency department in a tertiary care hospital with high C-reactive protein - Kunwar, Suman; Tuladhar, Eans Tara; Dubey, Raju Kumar; Bhattarai, Aseem; Raut, Mithileshwer; Niraula, Apeksha; Sharma, Vijay Kumar (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Patients presenting to the Emergency department represent a heterogeneous group with diverse acute and chronic morbid or multimorbid conditions indicating underlying inflammation. Inflammation is reflected by elevated levels of C-reactive protein (CRP) in the blood. As inflammatory conditions are frequently associated with anemia, characterized by a reduction in hemoglobin (Hb) concentration or red blood cell (RBC) count, this study aimed to assess the prevalence of anemia among patients admitted to emergency department at Tribhuvan University Teaching Hospital with inflammation, as indicated by high CRP, and to evaluate the correlation between CRP levels and anemia markers. Methods: A laboratory-based cross-sectional study was conducted using data from patients who underwent simultaneous testing for CRP, Hb, and RBC count between January 2023 and July 2023.CRP was measured by immunoturbidimetric method, Hb by sodium lauryl sulfate–hemoglobin (SLS-Hb) method and RBC was counted based on the principle of electrical impedance. Data were entered into Microsoft Excel® 2013 and analyzed using SPSS version 22 for both descriptive and inferential statistics. Results: A total of 609 patients had concurrent CRP, Hb, and RBC measurements. Elevated CRP levels (>1mg/L) were detected in 604(99.2%) patients. Among CRP positive individuals, 359(59.43%) were anaemic. Spearman rho correlation analysis showed a statistically significant but weak negative correlation of blood CRP concentration with hemoglobin (r=−0.094, p=0.02) and RBC count (r=−0.136, p=0.001). Conclusions: Anemia was found to be a common comorbid condition in more than half of the patients with inflammation as indicated by high CRP. However, CRP levels demonstrated only a weak inverse association with hemoglobin and RBC count, suggesting that while inflammation and anemia frequently coexist, the relationship between them is modest.